1997
DOI: 10.1097/00004647-199711000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Brain Injury is Mediated by the Activation of Poly(ADP-Ribose)Polymerase

Abstract: Poly(ADP-ribose)polymerase (PARP, EC 2.4.2.30), an abundant nuclear protein activated by DNA nicks, mediates cell death in vitro by nicotinamide adenine dinucleotide (NAD) depletion after exposure to nitric oxide. The authors examined whether genetic deletion of PARP (PARP null mice) or its pharmacologic inhibition by 3-aminobenzamide (3-AB) attenuates tissue injury after transient cerebral ischemia. Twenty-two hours after reperfusion following 2 hours of filamentous middle cerebral artery occlusion, ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
384
1
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 595 publications
(414 citation statements)
references
References 36 publications
(15 reference statements)
26
384
1
3
Order By: Relevance
“…Key evidence in establishing NO toxicity/PARP-1 activation as a major cytotoxic mechanism has accumulated from exclusively male animals with targeted deletions of nNOS (nNOSÀ/À) or PARP (PARPÀ/À). In each case, these knockouts are resistant to brain injury from focal and global cerebral ischemic insults, as are primary neuronal cell cultures derived from fetal brain obtained from mixed sexes (Huang et al, 1994;Eliasson et al, 1997;Endres et al, 1997;Samdani et al, 1997;Goto et al, 2002). Similar findings of neuroprotection using pharmacological inhibitors of nNOS and PARP-1 in male animals and mixed sex neuronal cell cultures have been widely reported (for reviews, see Beckman and Koppenol, 1996;Virag and Szabo, 2002;Virag et al, 2003;Ha and Snyder, 2000;Yu et al, 2003).…”
Section: Introductionmentioning
confidence: 63%
“…Key evidence in establishing NO toxicity/PARP-1 activation as a major cytotoxic mechanism has accumulated from exclusively male animals with targeted deletions of nNOS (nNOSÀ/À) or PARP (PARPÀ/À). In each case, these knockouts are resistant to brain injury from focal and global cerebral ischemic insults, as are primary neuronal cell cultures derived from fetal brain obtained from mixed sexes (Huang et al, 1994;Eliasson et al, 1997;Endres et al, 1997;Samdani et al, 1997;Goto et al, 2002). Similar findings of neuroprotection using pharmacological inhibitors of nNOS and PARP-1 in male animals and mixed sex neuronal cell cultures have been widely reported (for reviews, see Beckman and Koppenol, 1996;Virag and Szabo, 2002;Virag et al, 2003;Ha and Snyder, 2000;Yu et al, 2003).…”
Section: Introductionmentioning
confidence: 63%
“…Similarly, the earlier successes of PARP-1 inhibition or deletion strategies in reducing ischemic brain injury in vivo (Ding et al, 2001;Eliasson et al, 1997;Endres et al, 1997;Takahashi et al, 1999) may have their mechanistic basis in the secondary reduction in nuclear AIF translocation (Cao et al, 2003;Plesnila et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that di erent apoptosis inducers may through distinct apoptotic mechanisms, i.e., PARP-dependent or -independent. Supportive of this concept, two studies (Endres et al, 1997;Eliasson et al, 1997) have demonstrated that PARP-knockout mice are resistant to peroxynitriteinduced ischemic injury via inhibiting apoptotic cell death.…”
Section: Figurementioning
confidence: 99%